Analysis and Compensation for Systematical Errors in Airborne Microwave Photonic SAR Imaging by 2-D Autofocus - Min Chen; Xiaolan Qiu; Ruoming Li; Wangzhe Li; Kun Fu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
In the area of synthetic aperture radar (SAR), the ultrahigh resolution is always a continuous pursuit for researchers. To realize ultrahigh resolution, microwave photonics technology is an excellent solution since it has advantages of low transmission loss, ultrawide bandwidth (UWB), etc. However, with the improvement of resolution, new problems arise as the impact of more systematical errors becomes non-negligible, for example, the synchronization error between the transmit channel and the mixing channel, unknown system delay during signal reception, and the fluctuation of frequency for UWB signals. These factors will bring the degradation of the focusing quality of SAR images together with the motion errors and the trajectory measurement errors, causing not only residual range cell migration and azimuth phase error, but also higher order phase error along the range frequency dimension. In this article, we discuss the adverse influence of the above factors and give a detailed analysis of the 2-D phase error of the coarse focused image processed by range migration algorithm. Then, to compensate for the above unknown systematical errors, a 2-D autofocus method is proposed, and the effectiveness is validated by experiments on both simulated and real data.